STRATEGIES FOR CAPABILITY IMPROVEMENT OF FASHARKAN SURABAYA IN SUPPORTING INDONESIAN WARSHIP OPERATION READINESS - Bachtiar Efendi; Avando Bastari; Okol Sri Suharyo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
In carrying out increasingly complex tasks, and the development of naval technology, Fasharkan requires personnel who are professional in their fields and supported by technology-laden equipment in accordance with the development of the Indonesian Navy's defense equipment system. The purpose of this research is to determine an alternative strategy to increase the capability of Fasharkan Surabaya where Fasharkan Surabaya has a very strategic location because it is located in the Koarmada II environment which is the Home Base of the KRI which will carry out operations or finish operations. This study uses the integration of SWOT analysis and ISM (Interpretative Structural Modeling). SWOT analysis is used to formulate and provide alternatives in the strategy to increase the ability of Fasharkan Surabaya, while ISM is used to determine the order of priority for the selected strategy. Based on the results of the SWOT matrix analysis and weighting using the IFAS and EFAS matrices, the chosen strategy is the WO Strategy which consists of 9 (Nine) strategic steps, so the WO strategy is the first alternative. Furthermore, at the stage of classifying the elements in the WO strategy, the ISM method is used and from the results of the MICMAC analysis, it is found that there are 5 (five) levels of the hierarchical structure. In the hierarchical structure, it can be seen that the sub-strategy (WO2) is at level V, level IV sub-strategy (WO1) (WO3) and (WO7), level III sub-strategy (WO4) and (WO8), level II sub-strategy (WO6) and (WO9) and level I sub-strategy (WO5). Keywords: Benefit, Cost, Risk, Analytical Hierarchy Process, Benefit-Cost Ratio